The Fatty Acid Composition of Different Lamb Genotypes - Rózsáné Várszegi, Zsófia (Acta Agraria Debreceniensis, 2003)
We compares the fatty acid composition of five different genotypes. The maternal line was Hungarian Comb Merino x British Milksheep and this genotype was crossed with different terminal breeds, like: British Milksheep, Suffolk, Ile de France, German Mutton Merino, German Blackheaded. We compared the intramuscular fatty acid composition of different body parts like: leg, loin and shoulder. We can name that there are significant differences between the genotypes in the fatty acid composition. The suffolk crosses has the best UFA/SFA rate. In the meat of German Mutton Merino crosses has a high saturated fatty acid ratio, but there is a high polyunsaturated fatty acid ratio as well. There are only small differences between the meat parts in the view of fatty acid composition. Despite the small differences, the loin showed the best picture while the shoulder had the worst.